Kajian Jenis dan Populasi Mikoriza Vesikular Arbuskular (MVA) pada Lahan Tebu PG. Rejo Agung Baru Kota Madiun: Study of The Type and Population of Arbuscular Vesicular Mycorrhiza (MVA) in Sugarcane Field PG. Rejo Agung Baru Kota Madiun: Pertanian; Ilmu Tanah; Mikoriza - Abrorurizal Laduni; Arifin, Moch.; Priyadarshini, Rossyda (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
[IDENTIFICATION OF SPECIES AND POPULATION OF ARBUSCULAR MYCORRHIZAL FUNGI IN SUGARCANE PLANTATIONS AT PG. REJO AGUNG BARU, MADIUN]. Arbuscular Mycorrhizal Fungi (AMF) play an important role in enhancing plant root capacity for nutrient uptake. This study aimed to identify the species and determine the population of AMF in sugarcane fields at PG. Rejo Agung Baru, Madiun. Observations were conducted on four fields with different productivity levels: very high, high, moderate, and low. The research employed a quantitative descriptive approach with an exploratory method. Soil and root samples were analyzed to determine AMF species and population density, while the relationships between AMF populations and soil properties were examined using simple linear regression and t-tests. The results revealed that all sites contained the same AMF species, Glomus sp., which exhibited a high adaptability to various soil fertility conditions. The highest AMF population was observed in the very high productivity field (1.01 × 10⁷ spores/ha), whereas the lowest was found in the moderate productivity field (0.06 × 10⁷ spores/ha). Population variations were influenced by interactions among soil physical and chemical properties, particularly pH, organic carbon, total nitrogen, and clay fraction. Overall, this study demonstrates that the occurrence and population density of AMF, especially Glomus sp., are strongly affected by soil conditions. Optimal AMF populations were associated with soils characterized by near neutral pH, high organic matter content, low clay fraction, and moderate nitrogen levels, suggesting that these factors are critical for enhancing AMF activity in sugarcane cultivation. Full text pdf